Conductance Enhancement of Nano-Particulate Indium Tin Oxide Layers Fabricated by Printing Technique - Groß, Michael; Maksimenko, Ilja; Faber, Hendrik; Linse, N.; Wellmann, Peter (Nanotech 2008, Vol. 1-3, 2008)
To understand the mechanisms behind the conductance improvement and to fathom the limits we did some investigations: long-term resistance measurements gave an insight in oxygen vacancy balance concentration. From infrared absorption measurements we inferred the free charge carrier density and at present we carry out XPS measurements which yield information about the alteration of oxygen vacancy concentration. Considering these data we discuss two conductance improving mechanisms: The increase of the free charge carrier density by a rise of oxygen vacancy concentration as well as a release of trapped charge carriers from the aggregate surface
Keywords: ITO; nanoparticles; transmittance; conductance